Vício em smartphone e qualidade de vida em estudantes da área de saúde da Universidade Federal do Ceará - Citó, Erika Brasil Cavalcante (2021)
On January 2021, there were 4.32 bilions internet mobile users, from these 91.5% are smartphone users and this number increases year after year. The overuse of smartphones has been associated with musculoskeletal pain, sleep disorders, emotional problems and unsatisfaction regarding quality of life. The aim of this cross-sectional study was to evaluate smartphone addiction among health sciences students and its correlations with sleep quality, pain, neck disability, temporomandibular disorder (TMD) and quality of life. 349 students answered questionnaires about smartphone use pattern and the other variables included. Pearson tests and multilinear regression analysis were conducted considering smartphone addiction components as dependent variables. The mean age was 21.6 (SD= 3,58) years, 65.5% were women, 73.9% were classified as smartphone addicts. Considering the total score of each variable, there were no gender differences for smartphone addiction, sleep quality and quality of life, but women reported more neck disability and temporomandibular disorder. According to regression analysis, the smartphone use for more than 5h/day directly correlates to all addiction components. Temporomandibular disorder did not correlate to any smartphone addiction components. The more the satisfaction on quality of life physical and psychological domains, the less smartphone addiction, compulsion, functional impairment and withdrawal. The worst the sleep quality, the more smartphone addiction, functional impairment, compulsion and tolerance. Neck disability positively correlates to compulsion. The earlier the volunteer started using electronic devices, the more withdrawal. Older age correlated to tolerance. The students who reported moderate or severe pain showed less smartphone addiction. In conclusion: increased daily smartphone use may contributes to smartphone addiction development and negatively impacts the student´s health. It is quite important that the University community keeps aware of the negative impacts of SP overuse and addiction and works to adopt appropriate preventive support and harm reduction measures. Data regarding SP use and its influence on health parameters are important to establish health policies and to help technological industry to develop better products.